Impact De La Variabilité Pluviométrique Sur La Saison Culturale Dans La Zone De Production Cotonnière En Côte d’Ivoire - Dekoula, Charles Sékpa; Kouame, Brou; N’goran, Emmanuel Kouadio; Yao, Fernand Guy; Ehounou, Jean-Noël; Soro, Nagnin (European Scientific Journal, ESJ, 2018)
In Côte d’Ivoire, agriculture is mostly rain-fed. As a result, changes and variations of climate have considerable impacts on crops production including cotton production. This paper focuses on analyzing the effects of rainfall variations on the cropping season (useful rain season) of cotton in cotton production area of Côte d’Ivoire. A set of stationarity tests was applied to the Nicholson index using rainfall data of the period 1950-2000. Then, from a frequency analyses, the variability of rainfall and characteristic parameters of the cropping season was evaluated in terms of risks. The result shows a general downward trend of rainfall in the cotton growing area with years of breaks between 1964 and 1975. Moreover, spatial evolution of the cropping season parameters is a function of latitude. After the years of breaks, the beginning and the end of the cotton cropping season, which became respectively later and earlier, indicated that the length of useful rain season became shorter. The deficits of seasonal rainfall accumulations vary up to 60%. It is therefore necessary to update the crop calendar by taking into account variability of parameters of the useful rain season.